2021
DOI: 10.1155/2021/5579608
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Analysis between Gut Microbiota and Metabolites in Children with Systemic Lupus Erythematosus

Abstract: Systemic lupus erythematosus (SLE) is an autoimmune-mediated diffuse connective tissue disease characterized by immune inflammation with an unclear aetiology and pathogenesis. This work profiled the intestinal flora and faecal metabolome of patients with SLE using 16S RNA sequencing and gas chromatography-mass spectrometry (GC-MS). We identified unchanged alpha diversity and partially altered beta diversity of the intestinal flora. Another important finding was the increase in Proteobacteria and Enterobacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 40 publications
3
21
0
Order By: Relevance
“…Newly diagnosed treatment-naive SLE cases ( 44 ) and SLE patients that had not received glucocorticoid (GC) therapy ( 45 ) possessed a decrease of Lactobacillus in feces in Chinese and Egyptian patients compared with the healthy controls. However, SLE patients in most cohorts both active and remissive, both adults and children all manifested the enrichment of Lactobacillus in both fecal and oral sample in China and Netherlands ( 14 , 15 , 18 , 19 , 46 ) ( Table 1 ). Notably, Lactobacillus enriched in active SLE patients and lupus erythematosus skin lesions patients ( 47 ) as disease severity might play a role in abundance ( 14 ).…”
Section: Lactobacillus Are Altered In Sle Patientsmentioning
confidence: 99%
“…Newly diagnosed treatment-naive SLE cases ( 44 ) and SLE patients that had not received glucocorticoid (GC) therapy ( 45 ) possessed a decrease of Lactobacillus in feces in Chinese and Egyptian patients compared with the healthy controls. However, SLE patients in most cohorts both active and remissive, both adults and children all manifested the enrichment of Lactobacillus in both fecal and oral sample in China and Netherlands ( 14 , 15 , 18 , 19 , 46 ) ( Table 1 ). Notably, Lactobacillus enriched in active SLE patients and lupus erythematosus skin lesions patients ( 47 ) as disease severity might play a role in abundance ( 14 ).…”
Section: Lactobacillus Are Altered In Sle Patientsmentioning
confidence: 99%
“…In addition, Ruminococcaceae is a family of autochthonous and benign species [ 34 ] that produce short-chain fatty acids and has been well-illustrated to be responsible for the degradation of diverse polysaccharides and fibers [ 35 ]. The population size of Ruminococcaceae is inversely correlated with hepatic encephalopathy, nonalcoholic fatty liver disease, and systemic lupus erythematosus [ 35 , 36 , 37 ], and we detected a decrease in the immune system diseases pathway, which may be due to this bacterium. In the present study, we reported that E2 correlated with the g__Ruminococcus_torques_group .…”
Section: Discussionmentioning
confidence: 85%
“…Our findings of a decreased abundance of Ruminococcaceae in patients with SLE differed from the results of Wen et al . 39 Microbes in this family can produce short-chain fatty acids (SCFAs), 25 which are considered potential ‘orchestrators’ of the cross-talk between the gut microbiota and the host metabolism. 40 A reduction of these microbes may therefore lead to reduced SCFA production and disruptions of human metabolism.…”
Section: Discussionmentioning
confidence: 99%